Audio-Vestibular Alterations During the Phases of the Menstrual Cycle in Patients with Cochlear Implant - Apisa, Pasqualina; Auletta, Gennaro; Furia, Teresa; Riccardi, Pasquale; Laria, Carla; Malesci, Rita; Papa, Carmine; Sarnelli, Angelo; Marciano, Elio; Franzé, Annamaria (Archives of Clinical and Biomedical Research, 2019)
Background: The female hormones fluctuations in woman’s life play a dominant role in homeostasis of the body and can influence the psycho-neurological processes in different body systems. In particular, in the auditory system seems that hormonal alterations during the menstrual cycle can compromise the homeostasis of the labyrinthine fluids altering balance and/or hearing. Aims/Objectives: Our study aims to verify if hormonal changes during different menstrual phases may have an influence, in females with cochlear implants, on the trend of auditory and vestibular performances. Materials and methods: Tonal, speech audiometry, vestibular examination and a measure of cochlear implants electrodes impedances were realized in the follicular and luteal phases on a group of eight women who are at a fertile age, affected by profound sensorineural form of hearing loss and carrying a monolateral cochlear implant. Results: Audio-vestibular alterations, as well as, an increase of impedance electrodes are reported in the luteal phase. Conclusions: Our work suggests that audio-vestibular alterations are related to the different phases of the menstrual cycle with consequent variation also of the performances of the implant. It is very important to keep in mind this aspect to avoid negative results during rehabilitation.